2021
DOI: 10.3389/fpsyg.2021.661179
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of an Observational System for Penalty Kick Analysis in Football (OSPAF)

Abstract: The analysis of penalty kick has played an important role in performance analysis. The study aims are to get formal feedback on the relevance of variables for penalty kick analysis, to design and validate an observational system; and to assess experts’ opinion on the optimum video footage in penalty kick analysis. A structured development process was adopted for content validity, reliability and agreement on video usage. All observational variables included in OSPAF showed Aiken’s V values above the cut-off (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…The analysis of penalty kick performance in football has played an important role in sports analytics (Paterson et al, 2020 ; Noël et al, 2021 ; Pinheiro et al, 2021a , b ). Over the past 30 years, there have been several scientific studies that identify the motivational-, strategic-, anticipatory-, attention-, and perception-based factors that can mean a successful or failed penalty kick (Memmert and Nöel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of penalty kick performance in football has played an important role in sports analytics (Paterson et al, 2020 ; Noël et al, 2021 ; Pinheiro et al, 2021a , b ). Over the past 30 years, there have been several scientific studies that identify the motivational-, strategic-, anticipatory-, attention-, and perception-based factors that can mean a successful or failed penalty kick (Memmert and Nöel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 30 years, there have been several scientific studies that identify the motivational-, strategic-, anticipatory-, attention-, and perception-based factors that can mean a successful or failed penalty kick (Memmert and Nöel, 2020 ). Recent research focusing on the technical dynamics of penalty kicks has also identified multiple key variables that can differentiate the players strategy (Pinheiro et al, 2021b ) and enhance the overall chances of scoring a penalty kick (Jamil et al, 2020 ). The importance of the optimal performance of both the rival players during the penalty kick is paramount, especially since the introduction of the penalty shoot-out in major competitions to determine which team progresses after a drawn match (Fariña et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the performance of football players, a large amount of data is produced (Pinheiro et al, 2021). The literature has highlighted the importance of RT for success in football (Wojciech et al, 2021).…”
Section: Introductionmentioning
confidence: 99%